The aggregation of Brucella abortus occurs under microaerobic conditions and promotes desiccation tolerance and biofilm formation - Almiron, Marta A. (2012)
Brucella abortus causes brucellosis mainly in cattle. The infection is transmitted to humans by ingestion of animal products or direct contact with infected material. While the intracellular lifestyle of Brucella is well characterized, its extracellular survival is poorly understood. In nature, bacterial persistence is associated with biofilms, where aggregated cells are protected from adversity. The inability of Brucella abortus to aggregate under aerobiosis and that fact that the replicative niche of Brucella is characterized by microaerobic conditions prompted us to investigate the capacity of this pathogen to aggregate and grow in biofilms under microaerobiotic conditions. The results show that B. abortus aggregates and produces biofilms. The aggregates tolerate desiccation better than planktonic cells do, adhere and displace even in the absence of the lipopolysaccharide-O antigen, flagella, the transcriptional regulator VjbR, or the enzymes that synthesize, transport, and modify cyclic β (1,2) glucan.